2017
DOI: 10.1016/j.epidem.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of personal protective measures in reducing pandemic influenza transmission: A systematic review and meta-analysis

Abstract: The goal of this review was to examine the effectiveness of personal protective measures in preventing pandemic influenza transmission in human populations. We collected primary studies from Medline, Embase, PubMed, Cochrane Library, CINAHL and grey literature. Where appropriate, random effects meta-analyses were conducted using inverse variance statistical calculations. Meta-analyses suggest that regular hand hygiene provided a significant protective effect (OR=0.62; 95% CI 0.52-0.73; I=0%), and facemask use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 53 publications
0
137
0
16
Order By: Relevance
“…Past studies have shown that frequent, e↵ective handwashing can result in a comparable moderate reduction in infections [23,24,25]. A meta-analysis of the e↵ects of NPIs in reducing influenza transmission demonstrated that hand hygiene was significant in reducing influenza transmission, with an odds ratio of 0.62 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that frequent, e↵ective handwashing can result in a comparable moderate reduction in infections [23,24,25]. A meta-analysis of the e↵ects of NPIs in reducing influenza transmission demonstrated that hand hygiene was significant in reducing influenza transmission, with an odds ratio of 0.62 [26].…”
Section: Discussionmentioning
confidence: 99%
“…10 Plain hygienic measures have the strongest evidence. 10,11 Frequent hand washing and staying at home and avoiding contacts when sick are probably very useful. Their routine endorsement may save many lives.…”
Section: Extreme Measuresmentioning
confidence: 99%
“…Yet, in terms of the participants' attitudes toward wearing masks in pre-operative evaluations, only 11.8% stated that they wore masks continuously. Although studies have stated that healthcare providers prefer to not use personal protective equipment because their use increases emergency patient response time or because such equipment is impractical, healthcare providers should perform necessary medical interventions while protecting their own health as well [14][15][16]. In our study, a large proportion of the participants (43.9%) stated that they started wearing masks after the pandemic because of fear of disease transmission.…”
Section: Discussionmentioning
confidence: 72%